Pneumothorax secondary to septic pulmonary emboli in tricuspid endocarditis. Issue 12 (December 1992) - Corzo, J E; Lozano de León, F; Gómez-Mateos, J; López-Cortes, L; Vázquez, R; García-Bragado, F
Abstract : Two cases of pneumothorax secondary to pulmonary septic infarctions occurred in the course of tricuspid endocarditis in intravenous drug misusers. This unusual complication must be considered in patients with right sided endocarditis who develop pleuritic chest pain, haemoptysis, or breathlessness.